FIFTEENTH-CENTURY DECORATED TOMBSTONES FROM KUBACHI BEARING THE NAMES OF ALLAH, THE PROPHET MUHAMMAD AND CALIPH ALI IBN ABI TALIB - Mammaev, Misrihan Mamaevic (History, Archeology and Ethnography of the Caucasus, 2025)
This article presents an artistic, stylistic, and historical analysis of two 15-th century Muslim tombstones from Kubachi, each adorned with embossed late-Kufic Arabic inscriptions and floral ornamentation. The inscriptions on both tombstones feature the names of Allah, His Prophet Muhammad, and the fourth righteous caliph, Ali ibn Abi Talib. One tombstone (No. 1) bears a date of manufacture, corresponding to 837 Hijra (1433–34 CE). The other (No. 2) lacks a specific date but, based on paleographic characteristics of the Arabic decorative inscription and the style of the floral ornamentation, is attributed to the mid-15th century. On Tombstone No. 1, the inscriptions are arranged within circular embossed medallions positioned along the vertical axis of the central field. On Tombstone No. 2, the inscriptions are located at the left end of an embossed decorative Arabic inscription within an ornamental-epigraphic band that encircles the tombstone’s field in a semicircular arch. The inscription represents the Shahada, the Islamic declaration of monotheism: “There is no deity but Allah, and Muhammad is the Messenger of Allah.” The decorative inscriptions on both tombstones are carved against a background interwoven with relief floral motifs, characterized by a continuous wavy stem adorned with trifoliate leaves, semi-trifoliates, semi-palmettes, and other foliage. The ornamental designs of the tombstones are distinctive and expressive, suggesting they were crafted by two different artisans, likely skilled as both epigraphists and ornamentalists. The inclusion of the name of the righteous caliph Ali may indicate the influence of Shiism in Kubachi during this period.